Law and American Education: An Instructor's Guide - Palestini, Robert; Falk, Karen Palestini (Rowman & Littlefield Publishers, 2002)
Educators working with Palestini's textbook Law and American Education: a Case Brief Approach will find this comprehensive pedagogical tool useful. It contains the full briefs for the cases excerpted in the text, as well as diacritical and pedagogical suggestions. In addition to chapter-by-chapter methodology, the manual also contains a sample syllabus, sample examinations, and a supplement on the controversial issue of sexual harassment. This is an excellent companion for educators with no background in school law.